“Dissecting the role of T cell exhaustion in cancer progression: a multifaceted approach“ - Li, Xinyang; Song, Shiwen (Frontiers in Immunology, 2025)
This article thoroughly explores the crucial role of T cell exhaustion in the process of tumor immune escape, comprehensively explaining its key characteristics, such as dynamic plasticity, heterogeneity, and epigenetic reprogramming. The article first elaborates on the complex interaction between immune surveillance and tumor escape, and then clarifies the core position of T cells in anti-tumor immunity and the evolution of the “exhaustion” concept, covering various research fields from chronic infections to the tumor microenvironment (TME). It provides a detailed analysis of the origin, differentiation pathways, and dynamic plasticity of exhausted T cells, revealing the possibility of functional recovery under specific conditions. At the same time, the article analyzes the profound influence of various factors in the TME (such as metabolic stress, immune suppression networks, and stromal interaction interfaces) on the process of T cell exhaustion. It conducts in-depth research on the molecular characteristics of exhausted T cells (including surface marker characteristics, transcriptional regulatory networks, and metabolic reprogramming characteristics), providing potential therapeutic targets for precision medicine. In the clinical translation aspect, this study clarifies the cutting-edge exploration achievements of diagnostic biomarkers, such as the exhausted subtypes defined by single-cell multi-omics technology, the prognostic value of TCR clonal dynamics, and the innovation of treatment strategies, including the “re-mobilization window” theory in PD-1 blockade, the synergistic effect of epigenetic drugs, the temporal and spatial selection in metabolic intervention, and the application of engineered cell therapies. This study systematically integrates the latest progress in the field of T cell exhaustion, providing comprehensive and profound theoretical support and innovative ideas for addressing challenges in tumor immunotherapy.